Evidence for a role of srGAP3 in the positioning of commissural axons within the ventrolateral funiculus of the mouse spinal cord - Bacon, Claire; Endris, Volker; Andermatt, Irwin; Niederkofler, Vera; Waltereit, Robert; Bartsch, Dusan; Stoeckli, Esther T.; Rappold, Gudrun (PLOS ONE, 2011)
Slit-Robo signaling guides commissural axons away from the floor-plate of the spinal cord and into the longitudinal axis after crossing the midline. In this study we have evaluated the role of the Slit-Robo GTPase activating protein 3 (srGAP3) in commissural axon guidance using a knockout (KO) mouse model. Co-immunoprecipitation experiments confirmed that srGAP3 interacts with the Slit receptors Robo1 and Robo2 and immunohistochemistry studies showed that srGAP3 co-localises with Robo1 in the ventral and lateral funiculus and with Robo2 in the lateral funiculus. Stalling axons have been reported in the floor-plate of Slit and Robo mutant spinal cords but our axon tracing experiments revealed no dorsal commissural axon stalling in the floor plate of the srGAP3 KO mouse. Interestingly we observed a significant thickening of the ventral funiculus and a thinning of the lateral funiculus in the srGAP3 KO spinal cord, which has also recently been reported in the Robo2 KO. However, axons in the enlarged ventral funiculus of the srGAP3 KO are Robo1 positive but do not express Robo2, indicating that the thickening of the ventral funiculus in the srGAP3 KO is not a Robo2 mediated effect. We suggest a role for srGAP3 in the lateral positioning of post crossing axons within the ventrolateral funiculus.